Antidiabetic mellitus activity of low grade black tea in alloxan induced male albino mice - Deswati, Dytha Andri; Maryam, Zahra Nur (Jurnal Penelitian Teh dan Kina, 2016)
Tea (Camellia sinensis [L]) has a very potential character of quality and biological activities. Potential activity of black tea such as antidiabetic been proven by several studies. Grade of black tea was classified based on colour, shape, size and density of particles. Â This study aims to evaluate the most optimal antidiabetic activity of low grade black teas;BT II, DUST III, BBL and BTL in alloxan induced male albino mice. The results showed that liquor of black tea grade DUST III has blood glucose lowering activity with the most optimal percentage reduction 49.07% with a significant difference in the positive control group (p <0.05).